2011
DOI: 10.1038/ismej.2011.120
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of cyanobacterial biomass in anoxic tidal-flat sediments: a microcosm study of metabolic processes and community changes

Abstract: To follow the anaerobic degradation of organic matter in tidal-flat sediments, a stimulation experiment with 13 C-labeled Spirulina biomass (130 mg per 21 g sediment slurry) was conducted over a period of 24 days. A combination of microcalorimetry to record process kinetics, chemical analyses of fermentation products and RNA-based stable-isotope probing (SIP) to follow community changes was applied. Different degradation phases could be identified by microcalorimetry: Within 2 days, heat output reached its max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…This result is similar to a pervious study in the Yellow River Delta38. It could be explained by the low nutrient content in the Yellow River Delta that inhibits the growth of Cyanobacteria1839. The loss of Cyanobacteria in the sediment may also be due to the large amount of fine particles brought in by the Yellow River.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is similar to a pervious study in the Yellow River Delta38. It could be explained by the low nutrient content in the Yellow River Delta that inhibits the growth of Cyanobacteria1839. The loss of Cyanobacteria in the sediment may also be due to the large amount of fine particles brought in by the Yellow River.…”
Section: Discussionsupporting
confidence: 87%
“…A large number of microorganisms in tidal flats contribute to the diets of invertebrates, fish, and shorebirds that live in coastal ecosystems141516. Autotrophic bacteria, such as cyanobacteria, are abundant in tidal flats and have high rates of primary production, contributing to rapid carbon sequestration in tidal flats1718. Microbial communities in tidal flats are widespread and complex, having great effects on coastal ecosystems161920.…”
mentioning
confidence: 99%
“…600 vs. 350 hits Gbp 21 ), although ethanol fermentation genes were less abundant below the sulfatemethane transition zone. Little is known about alcohol concentrations and fluxes in marine and freshwater habitats, except that net production of ethanol was about half of net acetate production in slurry experiments with anaerobic tidal flat sediments (Graue et al 2012). Technical difficulties apparently have hindered efforts to measure alcohols in sediments and other environments (Beale et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although concentrations and fluxes of acetate are known to be high in anoxic sediments (Parkes et al 1989;Fukui et al 1997;Scholten et al 2000), the relative number of microbes producing this organic acid in sediments is not known. One of the few studies on other fermentation pathways found that net ethanol production was about half of net acetate production in anaerobic tidal flat sediments (Graue et al 2012). Variation in fermentation products over space and time has been shown to affect sulfatereducing bacteria (Boschker et al 2001).…”
mentioning
confidence: 98%
“…In sediment, sodium molybdate and bromoethanesulfonic acid (BES) are commonly used to inhibit sulfate reduction and trimethylamine is used as a specific substrate for methanogenesis [106]. In addition, using isothermal microcalorimetry in combination with 13 C labeled biomass allowed precisely following the organic matter degradation kinetic and the formation of by-products in a tidal-flat [107]. This approach allowed linking the phase of activity with specific metabolic processes.…”
Section: Application Of Isothermal Microcalorimetry In Environmentalmentioning
confidence: 99%